Pengaruh User Interface Quality, Information Quality, Perceived Security, Perceived Privacy, Belief, Dan Knowledge Terhadap Niat Beli Barang Di Website E-Commerce Di Indonesia. - Herison Halim (Universitas Tarumanagara, 2019)
E-Commerce or better known as electronic commerce is the dissemination, buying, selling, marketing of goods and services through electronic systems. In Indonesia, E-Commerce began to show a fairly rapid development. Factors Knowledge them about E-Commerce that makes the users of E-Commerce in Indonesia feel unsure to make transactions on the E-Commerce website. In addition to Knowledge factors, other factors such as User Interface Quality, Information Quality, Perceived Security and Perceived Privacy, are factors that can trigger a person to be able to perform transactions in E-Commerce. Then the factor of trust, attitude can also affect a person in doing transactions on E-Commerce website. This study aims to find out how the influence of user interface quality, information quality, perceived security, perceived privacy variables via trust variables, and belief variables, and knowledge through attitude variable to purchase intention in E-Commerce website in Indonesia. analysis method used is path analysis method, data source used is primary data. in this study also carried out the distribution of questionnaires as much as 300 respondents with the requirement that the prospective respondents must have or often give goods on E-Commerce website. The results There are variables that significantly affect the trust variables of User Interface Quality, Information Quality, Perceived Privacy. While other variables such as Belief, and Knowledge, significant effect on the Attitude someone to act or conduct transactions in E-Commerce website in Indonesia.